HAYK‖ CIVILIZATIONAL VISION AS A GEOPOLITICAL PROJECT OF THE FUTURE - Nersisyan, A. (SUSh Scientific Proceedings, 2025)
The content of the research problem posed in the article concerns the content of the future Armenian civilization in the new emerging world order and the geopolitical claim of the Armenian state that carries it. In accordance with this, it is proposed to formulate and supplement the scientific paradigm of the ―Hayk‖ civilization as the ideological basis of the national and state life process, which will also define a logical set of unified national and state life processes. All these are like new scientific paradigms based on interconnection with each other, complementing the scientific novelty put forward in the work. The urgency of posing such a research problem is dictated by the need to clearly define the place and role of the Armenian civilization in the emerging new world order. In accordance with the purpose of the work, a number of interrelated research tasks were set and solved. In particular, the possible directions of changing the form and content of state orders in the New World Order were considered in detail, which were discussed based on the logic of the transformation of the Armenian statehood. Accordingly, the ―Hayk‖ civilizational vision is proposed for the Armenian statehood as the ideological basis for both the organization of intra-communal (intra-state) life and the formation of external geopolitical ideas. To solve research problems, we used scientific methods of analysis, synthesis, generalization and reanalysis, comparative geographical, theoretical generalizations. The theoretical conclusions and recommendations obtained as a result of the research can be useful and applicable in practice in various area of public policy, the key of which is the educational sphere of social information exchange